1001 science questions answered (Reader's Digest Pty Limited, 2008)
Why do human beings cook their food? What does a gene look like? How do insects see the world? The answers to these intriguing questions and 998 more, ranging from astrology to zoology, are revealed in this fascinating book. Find out everything you want to know about the world around us: our mysterious universe; the human body; the secrets of nature; our changing planet; the everyday world, and the marvels of science and technology. This book will help you keep up with new phenomena and new technology and learn to understand the world around you in a fun and engaging way.